Model for building quality resilient health facility - Otchi, Elom Hillary; Gyawu, Nhyira; Buckle, Gilbert (Frontiers in Public Health, 2023)
The AfIHQSA Model is the model for building quality resilient health systems. It is proposed as a compliment to and in many instances as an alternative to the many other existing in ensuring a systematic and a sustained approach to improving outcomes in African health systems. It seeks to bring the necessary transformation to healthcare quality and patient safety and facilitate the attainment of desired outcomes. The model is unique in its iterative nature and how it places premium on sustaining the gains of improvement. The authors are concerned about the lack of sustainability of the many quality improvement efforts on the continent and how they all fade out into obscurity upon the exit of the proponents. Six iterative steps are proposed in the use of the model and these are: leadership commitment and buy-in; situational analysis of quality management capacity; systems strengthening for quality management; quality improvement interventions for care outcomes; standardization/accreditation/certification; and iterative monitoring, evaluation of performance of interventions and learning. Most of the quality interventions and efforts on the continent have failed because the steps in this model have not been sufficiently followed and addressed. The required strengthening of the various components of the health system necessary to sufficiently bear the weight of any quality intervention and guarantee sustainability of the gains is often ignored. As authors, we have therefore formally adopted the use of this model and plan to further continue evaluating and monitoring its utility and its generalizability in different institutions and countries.